Characterization of an Agile Coordination Office for IST companies - Pinto, José (2018)
Typically the Project Management Office activity is linked to the management and coordination of plan-driven projects, also known as waterfall or traditional projects. However, with the advent of agile methodologies in organizations of software development (the case of many information systems and technologies (IST)) no longer value the traditional PMO. It needs to be changed according to the agile values, so the organizations can extract benefits from such structure. These need to be fundamental changes in the responsibilities, practices and roles that a PMO should have. Also, it seems appropriate to rename it to something more descriptive and we chose to name it Agile Coordination Office (ACO). This paper presents the initial proposal of the ACO based on the existing literature. We propose the ACO to assume a behavior mainly supportive, due to the empowerment that every agile development team must have by definition. In addition, the architecture of this ACO aims to cover the various levels of management, from project and program up to the portfolio management. This division also reduces the complexity of ACO's implementation process and gives flexibility to rearrange the ACO over time.